1995
DOI: 10.1111/j.1432-1033.1995.tb20696.x
|View full text |Cite
|
Sign up to set email alerts
|

Separable Binding Sites for the Natural Agonist Endothelin-1 and the Non-Peptide Antagonist Bosentan on Human Endothelin-A Receptors

Abstract: A three-dimensional model for the transmembrane domains of human endothelin-A receptor was built using structural information from bacteriorhodopsin and sequence alignment to other guanine-nucleotide-binding regulatory(G) protein-coupled receptors. Based on this model, 18 amino acids located at the inside of the receptor were mutated and analyzed for binding of the natural ligand endothelin-1 and bosentan, a recently described potent orally active endothelin antagonist [Clozel, M., Breu, V., Gray, G., Kalina, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In vascular smooth muscle, ETA expression was reduced in treated children while ETB expression was increased to as great an extent in treated as in untreated children. We had to consider whether the presence of bosentan could mask the binding and localisation of antibodies to the receptors, but since the ET-1 receptor antagonists bind to the second transmembrane domain of receptor sites and endothelin antibodies typically bind to the C-terminus, which is a different domain, this seemed highly unlikely [18]. Serial reconstruction of peripheral arterial pathways indicated that progressive occlusion was associated with the formation, or recruitment, of more proximal bypass branches to supply the alveolar capillary bed, often via plexiform lesions, all of which retained an endothelium expressing ETA, ETB and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular smooth muscle, ETA expression was reduced in treated children while ETB expression was increased to as great an extent in treated as in untreated children. We had to consider whether the presence of bosentan could mask the binding and localisation of antibodies to the receptors, but since the ET-1 receptor antagonists bind to the second transmembrane domain of receptor sites and endothelin antibodies typically bind to the C-terminus, which is a different domain, this seemed highly unlikely [18]. Serial reconstruction of peripheral arterial pathways indicated that progressive occlusion was associated with the formation, or recruitment, of more proximal bypass branches to supply the alveolar capillary bed, often via plexiform lesions, all of which retained an endothelium expressing ETA, ETB and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…In general the molecular basis of action of these antagonists is poorly understood, and it is unclear whether it is similar to the well studied adrenergic or muscarinic cholinergic receptor antagonists (54 -56). Whereas there have been a number of studies of the molecular basis of action of nonpeptide antagonists for various GI hormone receptors (11)(12)(13)(14)(15), there are only a few studies of peptide antagonists (12,57,58) and almost none for peptoid antagonists (59). In this study we examined the molecular basis of action of the novel peptoid receptor antagonist PD168368, which is reported to be selective for the NMBR in the bombesin family of receptors (10,40,41).…”
Section: Wild-type Nmbr and Grpr-thementioning
confidence: 99%
“…They have been proven useful in helping to examine the role of these receptors in mediating various physiological and pathophysiological processes and they may be useful as therapeutic agents in such conditions as panic attacks (1,2,5). Whereas there have been a number of studies of the molecular basis of action of nonpeptide antagonists for various GI hormone/neurotransmitter receptors (11)(12)(13)(14)(15) within the heptahelical G protein-coupled receptors (GPCRs), almost nothing is known about the molecular basis of action for peptoid antagonists. For most small molecule ligands for GPCRs such as nonpeptide antagonists, transmembrane regions play an important role in determining the high affinity binding (16,17).…”
mentioning
confidence: 99%
“…However, because similar binding potency and selectivity ratio was found between human and rat ETA and ETB receptors, Ro 46-8443 seems to display few if any species differences, suggesting a highly conserved binding site on the ET receptors. Establishing the differences of this interaction to the recently described binding site of bosentan [31] will be valuable for the future design of new ETB receptor selective antagonists.…”
Section: Discussionmentioning
confidence: 98%